Creatinine–cystatin C ratio and mortality in cancer patients: a retrospective cohort study. Issue 4 (27th April 2022) - Jung, Chan‐Young; Kim, Hyung Woo; Han, Seung Hyeok; Yoo, Tae‐Hyun; Kang, Shin‐Wook; Park, Jung Tak
Abstract: Background: Muscle wasting is prevalent in cancer patients, and early recognition of this phenomenon is important for risk stratification. Recent studies have suggested that the creatinine–cystatin C ratio may correlate with muscle mass in several patient populations. The association between creatinine–cystatin C ratio and survival was assessed in cancer patients. Methods: A total of 3060 patients who were evaluated for serum creatinine and cystatin C levels at the time of cancer diagnosis were included. The primary outcome was 6‐month mortality. The 1‐year mortality, and length of intensive care unit (ICU) and hospital stay were also evaluated. Results: The mean age was 61.6 ± 13.5 years, and 1409 patients (46.0%) were female. The median creatinine and cystatin C levels were 0.9 (interquartile range [IQR], 0.6–1.3) mg/dL and 1.0 (IQR, 0.8–1.5) mg/L, respectively, with a creatinine–cystatin C ratio range of 0.12–12.54. In the Cox proportional hazards analysis, an increase in the creatinine–cystatin C ratio was associated with a significant decrease in the 6‐month mortality (per 1 creatinine–cystatin C ratio, hazard ratio [HR] 0.35; 95% confidence interval [CI], 0.28–0.44). When stratified into quartiles, the risk of 6‐month mortality was significantly lower in the highest quartile (HR 0.30; 95% CI, 0.24–0.37) than in the lowest quartile. Analysis of 1‐year mortality outcomes revealed similar findings. These associations were independent of confounding factors. The highest quartile was also associated with shorter lengths of ICU and hospital stay (both P < 0.001). Conclusions: The creatinine–cystatin C ratio at the time of cancer diagnosis significantly associates with survival and hospitalization in cancer patients.